A study of the balance between the poet Falih Rikabi and the poet Nawat Hassan Amin: Comparative study - Salman, Haidar Hadi (Al-Adab Journal, 2020)
The study of narrative in Arabic poetry has received a lot of modern monetary effort, and it has been included under various names such as story, story, story building, narrative performance, and dramatic construction in poetry, as if all these animals mean one thing, despite the differences between them. What matters to us here is the means of narrative construction that the creative uses in creating narrative text and showing it to exist through the description and narration, as well as dialogue, as the narration and description work together, but in a contradictory way, each of them his job, the narrative focuses on highlighting events in narrative work , The description seeks to reveal the objects and their components, people and their congenital print. The study was conducted in order to study the methods of narrative construction and its manifestations in the contemporary Iraqi poetry (a balance between the poet Falih al-Rikabi and the poet Nawat Hassan Amin). The study was divided between two sections: the first studied the description; the second came to study the dialogue. Its main findings. The researcher chose two prominent figures in the field of contemporary Iraqi poetry, and in the field of administrative work, which allows them to approach society in all its categories, as well as their love for the country, and their monitoring of the political and social issues experienced by the country, they carry the same love, attraction itself, nostalgia itself Stay away from him.